Automobile adsorption air-conditioning system using oil palm biomass-based activated carbon: A review - Mohammad Omar, Abdullah; Tan, Ivy Ai Wei; Lim, Leo Sing (Elsevier, 2011)
Refrigeration and air-conditioning technology are required to evolve in accordance to Montreal Protocol adopted in 1987 and Kyoto Protocol in 1997. This regulation concerns about the climate change in an attempt to phase-out chlorofluorocarbons (CFCs), followed by hydro chlorofluorocarbons (HCFCs) and then moving to 1,1,1,2-tetrafluoroethane (HFC-134a) starting 2011. This trend leads to a strong demand of new systems for air-conditioning, especially in automobile. Adsorption cooling system, among other proposed cooling technologies, has a very good potential for automobile applications. Hence, there exists a need for a creative design and innovation to allow adsorption technology to be practical for airconditioning in automobile in a near future. Oil palm shell-based activated carbon has been widely applied in various environmental pollution control technologies, mainly due to its high adsorption performance yet low cost. However, limited studies have been carried out on the characteristics and application of oil palm shell-based activated carbon in adsorption air-conditioning system. This paper is to present a comprehensive review on the past efforts in the field of adsorption air-conditioning systems for automobile. This work also aims to investigate the physicochemical properties of oil palm shell-based activated carbon and its feasibility for application in adsorption air-conditioning system. Some of the limitations are outlined and suggestions for future improvements are pointed out.